Acupuncture Attenuates Renal Sympathetic Activity and Blood Pressure via Beta-Adrenergic Receptors in Spontaneously Hypertensive Rats. (8th February 2017) - Yang, Jing-Wen; Ye, Yang; Wang, Xue-Rui; Li, Fang; Xiao, Ling-Yong; Shi, Guang-Xia; Liu, Cun-Zhi
Abstract : The sympathetic nervous system, via epinephrine and norepinephrine, regulates β -adrenergic receptor ( β -AR) expression, and renal sympathetic activation causes sustained increases in blood pressure by enhanced renin release. In this study, we aim to investigate the effect and underlying mechanism of acupuncture at Taichong (LR3) on renal sympathetic activity in spontaneously hypertensive rats. Unanesthetized rats were subject to daily acupuncture for 2 weeks. Mean blood pressure (MBP) and heart rate variability (HRV) were monitored at days 0, 7, and 14 by radiotelemetry. After euthanasia on the 14th day, blood and the kidneys were collected and subject to the following analyses. Epinephrine and norepinephrine were detected by ELISA. The expression of β -ARs was studied by western blotting and PCR. The renin content was analyzed by radioimmunoassay. 14-day acupuncture significantly attenuates the increase of MBP. The HRV indices, the standard deviation of all normal NN intervals (SDNN), and the ratio of the low-frequency component to the high-frequency component (LF/HF) were improved following acupuncture. Renal sympathetic activation induced upregulation of epinephrine, norepinephrine, and renin content were attenuated by acupuncture. In addition, acupuncture decreased β 1-AR expression and improved β 2-AR expression. These results indicated that acupuncture relieves the increased MBP via the regulation of renal sympathetic activity and β -ARs.